Reflection phase analysis of reflectarray antenna based on paper substrate materials - H. I Malik; M. Y. Ismail; S. R Masrol; Sharmiza Adnan (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This article presents an analysis of reflection loss and reflection phase behavior of a novel microstrip reflectarray antenna, embedded on paper substrate material. Two different paper substrates were first analyzed for dielectric material properties. A detailed analysis of scattering parameters of rectangular patch element with variable substrate heights has been carried out. Rectangular patch elements fabricated using adhesive copper tape over the paper substrate, show that a wide bandwidth is achieved compared to available conventional substrate materials. Fabricated patch elements over paper substrate material show a broadband frequency response of 340 and 290 MHz. It has also been demonstrated that the measured reflection phase ranges for both the substrate cover 310º and 294º at low phase gradients of 0.12 and 0.24 º/MHz respectively.